A genome-wide association study for age-related hearing impairment in the Saami - Van Camp, Guy; Van Laer, Lut; Huyghe, Jeroen; Hannula, Samuli; Van Eyken, Els; Stephan, Dietrich; Mäki-Torkko, Elina; Aikio, Pekka; Lysholm-Bernacchi, Alana; Sorri, Martti; Huentelman, Matthew J; Fransen, Erik (European Journal of Human Genetics, 2010)
International audience This study aimed to contribute to the elucidation of the genetic basis of age-related hearing impairment (ARHI), a common multifactorial disease with an important genetic contribution as demonstrated by heritability studies. We conducted a genome-wide association study (GWAS) in the Finnish Saami, a small ancient genetically isolated population without evidence of demographic expansion. The choice of this study population was motivated by its anticipated higher extent of linkage disequilibrium, potentially offering a substantial power advantage for association mapping. DNA samples and audiometric measurements were collected from 352 Finnish Saami individuals, aged between 50 and 75 years. To reduce the multiple testing burden, we applied principal component analysis to the multivariate audiometric phenotype. The first three principal components (PC) captured 80% of the variation in hearing thresholds, while maintaining biologically important audiometric features. All subjects were genotyped with the Affymetrix 100K chip. To account for multiple levels of relatedness among subjects, as well as population stratification, association testing was performed using a mixed model. We summarized top-ranking association signals for the three traits under study. The top-ranked SNP, rs457717 (P-value 3.55x10-7), was associated with PC3 and was localised in an intron of the IQ motif-containing GTPase-activating-like protein (). Intriguingly, SNP rs161927 (P-value 0.000149), seventh-ranked for PC1, was positioned immediately downstream of the metabotropic glutamate receptor 7 gene (). As a previous GWAS in a European and a Finnish sample set already suggested a role for GRM7 in ARHI, this study provides further evidence for the involvement of this gene.